TRANSAKSI YANG DIHARAMKAN DALAM ISLAM - Rofik, Eka Nur (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2020)
Conceptually, this paper discusses the reasons for the prohibited transaction in Islam. Through a literature review, the writer found the reasons for the prohibition of a transaction in Islam, among others: 1) haram li dzatihi, such as buying and selling pork, buying and selling alcoholic drinks, buying and selling carcasses and other illicit goods. 2) Haram li ghairihi, that are included in those categories: first, violates the an taraa din minkum principles, such as fraud. Second, violates the laa thadhlimuun wa laa tudhlamuun principles, such as gharar, hoarding of merchandise, manipulate requests riba, gambling, and the practice of bribery. Third, transactions that the contracts incomplete. Fourth, brokers, simsar, and speculation.